EUROPEAN ISOTHERMS MOVE NORTHWARDS BY UP TO 15 KM/YEAR: USING CLIMATE ANALOGUES FOR AWARENESS-RAISING - Martin Beniston (European Scientific Journal, ESJ, 2014)
Little use has been made up till now of the concept of climate analogues to link the present and the past, i.e., places whose current climate (“target” locations) is similar to that experienced some decades ago at distant locations (“reference” sites). Indeed, most research up till now has focused on analogues between present and future climates. Here we assess at what period in time the climate at a target station in Europe has reached – or will reach – that of a reference location, and show that the velocity of northward-moving isotherms can attain 15 km/year. Such displacements in space imply that temperatures at many target sites in Europe have already exceeded those experienced by stations located 300-500 km to the south in the last half-century. Such results can serve to better portray what a rapidly-changing climate means to a lay audience, and can provide useful information to the policy-making community.